Enhanced electrostatic spinning support layer composite diaphragm as well as preparation method and application thereof
By using electrospinning support layer composite separator in alkaline water electrolysis hydrogen production technology, the problems of insufficient hydrophilicity and gas isolation of traditional PPS separators are solved, the mechanical strength and stability are improved, and the surface resistance is reduced, and the More efficient hydrogen production process for electrolyzing water.
Patent Information
- Application Number
- CN202411540965.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-07
AI Technical Summary
Among the existing alkaline water electrolysis hydrogen production technology, traditional PPS separators perform poorly in hydrophilicity and gas isolation, resulting in increased risk of mixing hydrogen and oxygen, high surface resistance, affecting safety and energy consumption, and the coating layer It is easy to fall off and has poor stability, which limits the service life and energy efficiency of the diaphragm.
Using electrospinning support layer composite diaphragm, the electrospinning support layer and functional coating layer are prepared on the PPS film to form a reinforced diaphragm with a sandwich structure, which improves mechanical strength and stability, reduces surface resistance, optimizes hydrophilicity and Air isolation.
It significantly improves the mechanical strength and stability of the diaphragm, reduces the surface resistance, enhances safety and durability, improves the energy efficiency of the hydrogen production process of water electrolysis, and reduces the risk of mixing hydrogen and oxygen.
Smart Images

Figure CN119265630A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy materials, and in particular to an enhanced electrospinning support layer composite diaphragm and a preparation method and application thereof. Background Art
[0002] At present, alkaline water electrolysis (ALK) technology has occupied a place in green hydrogen projects due to its high technical maturity and low cost. However, ALK technology faces problems such as low current density, narrow operating range, and low hydrogen purity, which mainly come from the diaphragm materials used. Although the traditionally used PPS (polyphenylene sulfide) diaphragm has good alkali resistance and dimensional stability, it performs poorly in terms of hydrophilicity and gas barrier properties, resulting in an increased risk of mixing hydrogen and oxygen, which in turn affects safety and energy consumption.
[0003] Although the hydrophilicity and gas barrier properties of the diaphragm have been improved in recent years by coating a functional layer on the PPS substrate, there are still some challenges, such as the coating layer is easy to fall off and the stability is poor. In addition, the surface resistance of the PPS diaphragm is high, which also limits the energy efficiency of the hydrogen production process by electrolysis of water. Therefore, although the existing technology has improved the performance of the diaphragm to a certain extent, it still cannot completely overcome the above technical bottlenecks.
[0004] For example, the Zirfon UTP series diaphragms produced by AGFA of Belgium have a lower surface resistance (about 0.28Ω·cm 2 ) and a higher bubble point pressure (about 2.5 bar), but it is expensive (more than $300 / m 2 In comparison, although the domestic composite diaphragm has obvious price advantages (about 600 to 900 yuan / m 2 ), and has reached international standards in key performance indicators, but there are still problems such as coating shedding and insufficient stability.
[0005] While improving the performance of the diaphragm, the existing technology has not completely solved the problems of coating shedding and poor stability, which directly affects the service life of the diaphragm and the energy consumption of hydrogen production by electrolysis of water. In addition, the problem of high surface resistance has not been effectively solved, resulting in high energy consumption. In summary, although the existing technology has been improved in some aspects, there is still a lot of room for improvement in mechanical strength, surface resistance, stability, etc. Summary of the invention
[0006] In order to solve the above technical problems, the purpose of the present invention is to provide an enhanced electrospinning support layer composite diaphragm and its preparation method and application. The present invention introduces an electrospinning support layer to prepare an enhanced electrospinning support layer composite diaphragm with a sandwich structure. The prepared diaphragm has good stability, improves the mechanical strength of the diaphragm material, reduces the surface resistance, and improves the safety and durability of the diaphragm material, improves the performance of the composite diaphragm, and improves the energy efficiency in the process of hydrogen production by electrolysis of water.
[0007] The technical solution of the present invention to solve the above technical problems is as follows:
[0008] The first object of the present invention is to provide an enhanced electrospinning support layer composite membrane, which comprises a first coating layer, a composite layer, and a second coating layer, wherein the composite layer is located between the first coating layer and the second coating layer; the composite layer comprises an electrospinning support layer and a PPS film.
[0009] The beneficial effects of the present invention are as follows: the enhanced electrospinning support layer composite diaphragm with a sandwich structure formed by the first coating layer, the composite layer and the second coating layer achieves a balance between the mechanical strength and functionality of the diaphragm, thereby improving the overall performance of the diaphragm.
[0010] Furthermore, when the enhanced electrospinning support layer composite membrane is placed in the electrolytic cell, viewed from the cathode side to the anode side, the structure of the enhanced electrospinning support layer composite membrane is, in sequence, the first coating layer, the electrospinning support layer, the PPS membrane, and the second coating layer.
[0011] Based on the above technical solution, the present invention can also be improved as follows.
[0012] Furthermore, the thickness of the enhanced electrospinning support layer composite membrane is 700 μm to 1200 μm, and the thickness of the electrospinning support layer is 10 μm to 50 μm.
[0013] The beneficial effects of adopting the above further scheme are: the thickness of the electrospun layer affects the mechanical strength, surface resistance, porosity, stability and gas barrier properties of the diaphragm. (1) A thicker electrospun layer can significantly improve the mechanical strength of the diaphragm and reduce the risk of breakage due to external forces during use. (2) A thinner electrospun layer will lead to a higher surface resistance, while an appropriate thickness can achieve a lower surface resistance. (3) If the thickness of the electrospun layer is too thin, the air permeability will decrease, while if it is too thick, the porosity of the diaphragm will increase, affecting the stability and gas barrier properties of the diaphragm. (4) If the thickness of the electrospun layer is too thin, the diaphragm will be unstable and easy to fall off; while an appropriate thickness will enhance the stability of the diaphragm.
[0014] The second object of the present invention is to provide a method for preparing an enhanced electrospinning support layer composite membrane, the method comprising the following steps:
[0015] (1) Preparation of the composite layer: a layered metal double hydroxide (LMOH) and polysulfone (PSU) are mixed and dissolved to obtain a spinning solution, a PPS film is used as a receiving substrate, and the spinning solution is used to perform electrospinning on one side of the PPS film to prepare an electrospinning support layer, thereby obtaining a composite layer;
[0016] (2) Preparation of coating layer: The functional material is mixed with a dispersant and dissolved to form a coating slurry, and the coating slurry is evenly coated on both sides of the composite layer. The coating slurry on both sides is solidified by phase inversion treatment to obtain a first coating layer and a second coating layer, thereby forming an enhanced electrospinning support layer composite diaphragm with a stable sandwich structure.
[0017] The beneficial effects of the present invention are as follows: the present invention prepares an enhanced electrospinning support layer composite diaphragm through the preparation of an electrospinning support layer, the preparation of a first coating layer and a second coating layer, and a curing treatment. The electrospinning support layer improves the mechanical strength of the diaphragm and reduces the risk of the coating layer falling off. The functional coating material reduces the risk of hydrogen and oxygen mixing by optimizing the hydrophilicity and gas barrier properties. The curing treatment ensures that the coating is fully cured by natural drying and curing, thereby improving the stability of the diaphragm.
[0018] Furthermore, the voltage of the electrospinning is 15 kV to 20 kV, the temperature is 20° C. to 30° C., the time is 25 minutes to 45 minutes, and the spinning flow rate is 2 mL / h to 5 mL / h.
[0019] Furthermore, the receiving distance between the needle used in the electrospinning and the PPS film is 15 cm to 20 cm; the model of the needle used in the electrospinning is 22G to 25G.
[0020] The beneficial effect of adopting the above further solution is that the performance of the diaphragm is optimized by adjusting the voltage and receiving distance of the electrospinning.
[0021] Furthermore, in step (1), the weight ratio of the layered metal double hydroxide to the polysulfone is 1-2:1-2.
[0022] The beneficial effect of adopting the above further solution is that the present invention improves the mechanical strength and stability of the diaphragm and reduces the risk of the coating layer falling off by optimizing the structure of the supporting layer.
[0023] Furthermore, in step (2), the weight ratio of the functional material to the dispersant is 1-2:1-2.
[0024] Furthermore, the specific steps of the phase inversion treatment are as follows: the coating layer is naturally dried and cured at room temperature for 20h-26h.
[0025] The beneficial effects of adopting the above further solution are: ensuring that the coating is fully cured and improving the stability of the coating layer. At the same time, natural drying and curing can simplify the process flow and reduce production costs.
[0026] Furthermore, the functional material includes at least one of layered metal double hydroxide, diatomaceous earth, silicon dioxide, barium titanate, and nanocellulose; and the dispersant includes at least one of polysulfone, polyvinyl alcohol, polyacrylamide, and polyethylene glycol.
[0027] The beneficial effect of adopting the above further scheme is that after the functional coating material is modified by the hydrophilic group of the dispersant, the hydrophilicity and gas barrier property of the diaphragm are improved, and the risk of mixing of hydrogen and oxygen is reduced.
[0028] The third object of the present invention is to provide an application of an enhanced electrospinning support layer composite membrane, and to use the enhanced electrospinning support layer composite membrane in the process of producing hydrogen by electrolysis of water.
[0029] The beneficial effects of the present invention are as follows: the diaphragm prepared by the present invention has low surface resistance, good stability, improved hydrophilicity and gas barrier properties, and is applied in the process of producing hydrogen by electrolysis of water to improve energy efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a scanning electron microscope image of the enhanced electrospinning support layer composite membrane prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.
[0032] Example 1: Preparation of enhanced electrospinning support layer composite membrane
[0033] (1) Electrospinning: Mix LMOH and PSU in a weight ratio of 1:1, and add 10 ml of deionized water to make a spinning solution. Load the spinning solution into the syringe of the electrospinning device (model NW103; manufacturer Jiangsu Biaojiao). Turn on the electrospinning device and adjust the voltage to 20 kV. Place a 700 μm PPS film (Tianjin Polytechnic University) on the collecting plate as a receiving substrate, use a 24G needle, and the distance from the receiving substrate is 15 cm. Use the spinning solution to electrospin on one side of the PPS film at 25°C and a spinning flow rate of 3 mL / h for 30 minutes to prepare a 10 μm electrospinning support layer to obtain a composite layer;
[0034] (2) Coating: LMOH and PSU are mixed in a weight ratio of 1:1, and 10 ml of deionized water is added to prepare a coating slurry. The coating slurry is uniformly stirred until it is completely dissolved. The prepared coating slurry is evenly applied to both sides of the composite layer using a scraper. The coating slurry on both sides is naturally dried and cured at room temperature of 25°C for 24 hours through phase inversion treatment to obtain the first coating layer and the second coating layer, that is, to form a sandwich structured reinforced electrospinning support layer composite diaphragm.
[0035] The enhanced electrospinning support layer composite membrane prepared in Example 1 was tested using a scanning electron microscope (Guangzhou Beituo Science and Technology Co., Ltd.; SEC desktop scanning electron microscope SNE-3200M). The results are as follows: Figure 1 shown.
[0036] Embodiment 2-10:
[0037] The difference between Example 2-10 and Example 1 is that the electrospinning voltage, electrospinning layer thickness, collection distance, time, temperature, and curing time are different. The remaining raw materials and steps are the same as those in Example 1, as shown in Table 1 below:
[0038] Table 1
[0039]
[0040] Comparative Example 1:
[0041] In this comparative example, 700 μm PPS was used as the separator without any other treatment.
[0042] Comparative Examples 2-9:
[0043] Comparative Examples 2-9 differ only in electrospinning voltage, collection distance, time, temperature, and curing time, and the remaining raw materials and steps are the same as those of Example 1, as shown in Table 2 below:
[0044] Table 2
[0045]
[0046] Test example:
[0047] The membranes prepared in Examples 1-10 and Comparative Examples 1-9 were tested for their surface resistance, bubble point pressure, porosity, mechanical strength, and stability.
[0048] The test method is as follows:
[0049] (1) Surface resistance: The surface resistance of the diaphragm was measured using a surface volume resistivity tester (Ningbo Ruike Micro Intelligent Technology Co., Ltd.; FT-303). The test voltage was set to 10 V and the test area was 1 cm. 2 .
[0050] (2) Bubble point pressure test method: The bubble point pressure of the diaphragm was measured using a bubble point pressure tester (GBT 32361; Jinan Shanjing Instrument Equipment Co., Ltd.). The test liquid was deionized water and the test pressure range was 0-10 bar.
[0051] (3) Porosity test method: The porosity of the diaphragm was measured by scanning electron microscope SEM-2000 (JF-2900V; Xiamen Jingfan Technology Co., Ltd.) with a magnification of 5000 times and a resolution of less than 5 nm.
[0052] (4) Mechanical strength test method: The mechanical strength of the diaphragm was measured using an Amphenol tester (TT-3000; Amphenol), wherein the tensile speed was 5 mm / min and the maximum load was 500 N.
[0053] (5) Stability test method: Place the diaphragm sample in an alkaline solution with a pH of 13 and a temperature of 80°C. After soaking for 72 hours, measure the surface resistance, bubble point pressure and porosity again.
[0054] Table 3
[0055]
[0056]
[0057] From Table 3, we can get:
[0058] (1) The surface resistance of Examples 1 to 10 is between 0.17 and 0.22 Ω·cm 2 It is significantly better than the comparative example 1 (>1.0Ω·cm 2 ) and other comparative examples. The bubble point pressures of Examples 1 to 10 are between 5.0 and 5.6 bar, which are significantly higher than the bubble point pressures of Comparative Examples 2 to 9 (3.5 to 4.5 bar).
[0059] (2) The porosity of Examples 1 to 10 is between 70% and 76%. The functional coating material of the present invention reduces the risk of mixing hydrogen and oxygen by optimizing the hydrophilicity and gas barrier properties, so that Example 10 exhibits good air permeability and stability.
[0060] (3) The mechanical strength of Examples 1 to 10 is between 230 and 260 N, which is significantly better than the mechanical strength of Comparative Examples 1 to 9 of 150 to 230 N. After the diaphragms prepared in Examples 1 to 10 were immersed in a simulated alkaline water electrolysis environment for 72 hours, the stability of Examples 1 to 10 was "excellent", while the stability of Comparative Examples 1 to 9 was only "medium" or "poor". It can be seen that the electrospinning support layer prepared by the present invention improves the mechanical strength of the diaphragm and reduces the risk of the coating layer falling off.
[0061] In summary, the diaphragm prepared by the present invention has low surface resistance, good stability, improved hydrophilicity and gas barrier properties, and is applied in the process of hydrogen production by electrolysis of water to improve energy efficiency.
[0062] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. An enhanced electrospinning support layer composite membrane, characterized in that: The enhanced electrospinning support layer composite diaphragm comprises a first coating layer, a composite layer, and a second coating layer, wherein the composite layer is located between the first coating layer and the second coating layer; the composite layer comprises an electrospinning support layer and a PPS film.
2. The enhanced electrospinning support layer composite membrane according to claim 1, characterized in that: The thickness of the enhanced electrospinning support layer composite diaphragm is 700 μm to 1200 μm, and the thickness of the electrospinning support layer is 10 μm to 50 μm.
3. A method for preparing an enhanced electrospinning support layer composite membrane, characterized in that: The method comprises the following steps: (1) Preparation of the composite layer: a layered metal double hydroxide and polysulfone are mixed and dissolved to obtain a spinning solution, a PPS film is used as a receiving substrate, and the spinning solution is used to perform electrospinning on one side of the PPS film to prepare an electrospinning support layer to obtain a composite layer; (2) Preparation of coating layer: The functional material is mixed with a dispersant and dissolved to form a coating slurry, and the coating slurry is evenly coated on both sides of the composite layer. The coating slurry on both sides is solidified by phase inversion treatment to obtain a first coating layer and a second coating layer, thereby forming an enhanced electrospinning support layer composite diaphragm with a sandwich structure.
4. The method for preparing a reinforced electrospinning support layer composite diaphragm according to claim 3, characterized in that: The voltage of the electrostatic spinning is 15 kV to 20 kV, the temperature is 20° C. to 30° C., the time is 25 minutes to 45 minutes, and the spinning flow rate is 2 mL / h to 5 mL / h.
5. The method for preparing a reinforced electrospinning support layer composite membrane according to claim 4, characterized in that: The receiving distance between the needle used in the electrospinning and the PPS film is 15 cm to 20 cm; the model of the needle used in the electrospinning is 22G to 25G.
6. The method for preparing a reinforced electrospinning support layer composite membrane according to claim 3, characterized in that: In step (1), the weight ratio of the layered metal double hydroxide to the polysulfone is 1-2:1-2.
7. The method for preparing a reinforced electrospinning support layer composite diaphragm according to claim 3, characterized in that: In step (2), the weight ratio of the functional material to the dispersant is 1-2:1-2.
8. The method for preparing a reinforced electrospinning support layer composite diaphragm according to claim 3, characterized in that: The specific steps of the phase inversion treatment are as follows: the coating layer is naturally dried and cured at room temperature for 20h-26h.
9. The method for preparing a reinforced electrospinning support layer composite diaphragm according to claim 3, characterized in that: The functional material includes at least one of layered metal double hydroxide, diatomaceous earth, silicon dioxide, barium titanate, and nanocellulose; the dispersant includes at least one of polysulfone, polyvinyl alcohol, polyacrylamide, and polyethylene glycol.
10. An application of an enhanced electrospinning support layer composite membrane, characterized in that: The enhanced electrospinning support layer composite diaphragm according to any one of claims 1 to 2 is used in the process of producing hydrogen by electrolysis of water.